Quantification of major milk proteins using ultra-performance liquid chromatography tandem triple quadrupole mass spectrometry and its application in milk authenticity analysis. (January 2022) - Hao, Xingkai; Fu, Linglin; Shao, Liangliang; Chen, Qi; Dorus, Brian; Cao, Xudong; Fang, Fang
Abstract: An authenticity-based method was developed to detect economically motivated adulteration (EMA) in milk. To achieve this goal, 46 peptides released from trypsin digested milk proteins were identified and marker peptides were further selected based on their digestibility and stability characteristics to allow further quantifications of the milk proteins in the original samples using an isotope-dilution ultra-performance liquid chromatography tandem triple quadrupole mass spectrometry (UPLC-TQMS). Furthermore, to detect EMA in milk samples, 22 authentic milk powder samples were analyzed using the isotope-dilution UPLC-TQMS, and an authenticity threshold value --70.26 g/100 g as the content of all five major milk proteins to total protein—was established to evaluate milk samples with high adulteration risks. Finally, the threshold value was validated using soy protein adulterated milk samples. Results showed that the reported authenticity-based method was sensitive enough to detect the tampering of milk samples with as little as 10 % soy protein added. It is clear that this newly developed authenticity-based detection method is a powerful tool to detect unknown adulteration risks in milk samples. Highlights: Selected 5 marker peptides from 46 identified peptides based on their digestibility and stability characteristics. Established and validated an isotope-dilution UPLC-TQMS method to quantitatively analyze major milk proteins. Developed a milk authenticity threshold value to detect milk adulterations. Validated the threshold value using artificially adulterated milk samples.